The power of a man to beat his wife: a critical study of the book “Darb al-Mar’ah” of Abdul Hamid Abu Sulayman = سلطة الرجل في ضرب زوجته الناشز:دراسة نقدية لكتاب "ضرب المرأة" لعبد الحميد أبي سليمان - Zakariyah, Habeebullah (Usuli Faqih Research Centre, 2018)
This paper aims at studying the extent to which a man has the right to beat his disobedient wife in Islamic jurisprudence. The word Al-Ḍarb in Arabic language has different literal meanings according to the context in which it is used. In this case, this paper is attempts to study the perspectives of Abu Sulayman on the meaning of beating (Al-Ḍarb) in the Quranic text by studying his book Ḍarb alMar’ah: wasīlah lihalli al-khilāfāt al-Zawjiyyah. The researcher used the critical analysis method in studying Abu Sulayman's perspective on the meaning of beating (Al-Ḍarb). The research is concluded with a number of results, the most important of which is illustrated in the definition of beating (el-Ḍarb) as explained in the Qur’anic texts. In the Qur’anic texts, el-Ḍarb means a touch or slight hitting. However, the permission given to the husband to beat his disobedient wife is bound by the interest which is accompanied by other mandate provisions (al-Ahakām el-taklīfiyyah). Therefore, despite the licitness of beating, it can as well be undesirable or forbidden. The research has also figured out that the government is authorized to restrict or prevent such permissibility if it considers and sees that it does not achieve the objectives of Shari’ah for which it was enacted. *********************************************************** تهدف هذه الورقة إلى دراسة مدى سلطة الرجل في ضرب زوجته الناشز في الفقه الإسلامي، وحيث إن الضرب في لغة العرب يراد به عدة معان على حسب السياق الذي جاء فيه فإن هذه الورقة تسعى إلى دراسة وجهة نظر أبي سليمان في المراد بالضرب في النص القرآني، وذلك في كتابه: ضرب المرأة: وسيلة لحل الخلافات الزوجية، واستخدم الباحث منهج التحليل النقدي في دراسة وجهة نظر أبي سليمان حيال المراد بالضرب. وخلصت هذه الورقة إلى جملة من النتائج أهمها: أن المقصود بالضرب في النصوص القرآنية هو الإصابة، وأن إباحة ضرب الرجل زوجته الناشز منوط بالمصلحة، وتتجاذبه الأحكام التكليفية الأخرى، وعليه فالضرب وإن كان مباحا إلا أنه يمكن أن يكون مكروها أو محرما، كما خلصت الدراسة إلى للحاكم السلطة في تقييد هذه الإباحة أو منعها إذا رأت أنه لا تحقق المقصد الشرعي الذي شرعت لأجله.